Influencer Marketing in Digital Era: Does It Really Works? - Daniel Hermawan (Research Synergy Foundation, 2020)
The increasing number of social media users creates new opportunities in the marketing world. Marketing, which initially focused on the product (product-oriented), now has to be transformed into consumer-oriented marketing with many information channels owned by consumers. Consumers are becoming more critical of the products/services offered by companies with the many choices they have. The existence of influencers is a bridge or communication medium that connects companies with consumers in the digital era. Through personality, authenticity, and honesty given by influencers, consumers are expected to be more attached and aware of the existence of a brand. Not infrequently, companies take advantage of influencers in product/service marketing programs in introducing a brand. Influencers become digital advocates who represent brands through endorsement programs. This research will discuss (1) the phenomenon of influencer marketing in the digital era, (2) the types of influencers and the characteristics of consumers who follow them, (3) the use of influencers in marketing activities in the digital era. The study was conducted through Pentad analysis with qualitative methods. The study found that influencer marketing can be an effective marketing method by leveraging the influencer's charisma, personality, attitude, and lifestyle in representing the brand.